Peran Orang Tua dalam Internalisasi Pendidikan Nilai-Nilai Kehidupan bagi Anak Usia Dini - Ali, Noor Rochmad (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2016)
Early childhood is future generations. The next generation leaders civilization. They will feel the waves changes walking so fast and is difficult to predict of the 21st century. At the age of 100 years the independence of indonesia, 2045 year, they to become 35-44 years. The future generations expected to position himself as problem resolver, have leadership spirit, independent, about the environment. The character that will contribute become agents of change in the 21st century. Planting life of values can be established through the knowledge gained from parents. The role of the responsibility of the parents very important in living values education. Education of children could not entirely up to the schools. It was because the role of parents having the percentage equal to school or of the society 30 %. Early childhood generally have values in him. Parents have a responsibility important in life those values are. Revives value the child had a profound impact on the environment. Children will have the effect of values to their peers and environment when those values are have finished in him.